PREVALENCE OF CUTANEOUS MANIFESTATIONS OF DIABETES MELLITUS - Ahmed, Khurshid; Muhammad, Zardad; Qayum, Iftikhar (Journal of Ayub Medical College Abbottabad, 2009)
Background: Diabetes mellitus (DM) is a clinical syndrome characterized by hyperglycaemia due to absolute or relative insulin deficiency. The aim of this study was to evaluate the frequency of skin manifestations in patients with diabetes mellitus of this area. This descriptive study was conducted in medical out patient door of District Headquarter Hospital Battgram from January 2008 to July 2008. Methods: A total of 350 diabetic (types 1 and 2) patients over 15 years of age attending the medical OPD of DHQ Hospital were examined in detail for skin manifestations of the disease. Results: Three hundred and fifty diabetic (type-1 and type-2) patients (193 females and 157 males) enrolled in this study. Mean age of the patients was 54±8.53 years. Duration of diabetes was between 1-12 years; 320 patients had type-2 and 30 patients had type-1 diabetes mellitus. Patients with uncontrolled disease were 327 and 23 patients showed adequate glycaemic control. Seventy-six percent of patients had cutaneous manifestations. The skin manifestations observed were: skin infections 30.9%, foot gangrene and ulcers 12.9%, pruritus 7.1%, vitiligo 5.7%, yellow skin 4.2%, diabetic dermopathy 4.2%, skin tags 3.7%, acanthosis nigricans 2.9%, eruptive xanthomas 2.6%, necrobiosis lipoidica diabeticorum 1.4%, diabetic bullae 0.6%, and pigmented purpuras in 0.3% patients. Conclusions: Cutaneous manifestations were quite common in the diabetics of this area. Keywords: Diabetes mellitus, cutaneous manifestations, IDDM, NIDDM